2019
DOI: 10.1155/2019/9694602
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Facility-Based Childbirth in Indonesia

Abstract: Background. Reducing maternal mortality remains a significant challenge in Indonesia, especially for achieving the country’s Sustainable Development Goals (SDGs) by 2030. One of the challenges is increasing delivery at healthcare facilities to ensure safe and healthy births. In Indonesia, research on factors affecting women’s use of facility-based childbirth services is scarce. Objective. This study was conducted to identify the determinants of facility-based deliveries in Indonesia. Methods. This study used d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
45
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(56 citation statements)
references
References 27 publications
7
45
0
4
Order By: Relevance
“…The existing literature on the determinants of facilitybased delivery is extensive [10][11][12][13][14][15][16][17][18][19][20]. Results from this literature point to various cultural, economic and social reasons that facilitate or deter the use of health facilities for delivery.…”
Section: Introductionmentioning
confidence: 99%
“…The existing literature on the determinants of facilitybased delivery is extensive [10][11][12][13][14][15][16][17][18][19][20]. Results from this literature point to various cultural, economic and social reasons that facilitate or deter the use of health facilities for delivery.…”
Section: Introductionmentioning
confidence: 99%
“…The same conditions apply to Indonesia (Mubasyiroh, Nurhotimah and Laksono, 2016) (Laksono, Wulandari and Soedirham, 2019b). Not only in the use of childbirth services, but also in the use of antenatal care services (Efendi et al, 2019).…”
Section: Discussionmentioning
confidence: 96%
“…In general, the level of education is directly proportional to wealth status and knowledge of the danger signs of pregnancy. The higher the level of education, the better the wealth status, the more understanding about the danger signs of pregnancy, the more will increase the utilization of health care facilities in childbirth (Shahabuddin et al, 2016) (Asseffa, Bukola and Ayodele, 2016) (Efendi et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The higher the level of education, the better the wealth status, the more understanding about the danger signs of pregnancy, the more will increase the utilization of health care facilities in childbirth [34] [41]. Not only in the use of childbirth services, but also in the use of antenatal care services [36].…”
Section: Discussionmentioning
confidence: 99%
“…[35][36). Various studies in several countries on the impact of ownership of health insurance have found findings that have increased the use of health services that is far better[37][38][39][40].…”
mentioning
confidence: 99%